Paying It Forward or Giving Back? Women's Sharing Networks in Siberia. (July 2019) - Ziker, John P.; Fulk, Karen S.
Subsistence food sharing in Ust'-Avam (Taimyr Region, Russian Federation) is analyzed in light of Arctic research on sharing and current debate. Cultural traditions such as food sharing practices are widespread across indigenous communities in the Arctic and are arguably fundamental to the sustainability of indigenous Arctic cultures and their ability to buffer against environmental disequilibrium. Sharing diaries from 10 respondents over 12 weeks in August and October 2001, describe 162 distributions among 69 household dyads. Independent variables, including household relatedness, reciprocal sharing, and interaction effects, influence the documented food sharing pattern. Economic need and social association also influence sharing. Indicators of risk buffering are weaker than in two previous analyses of food sharing in Ust'-Avam that focus on primary distributions after the hunt and interhousehold meal sharing. Consideration of sharing by nonhunters provides an opportunity to examine explanatory hypotheses of food sharing, illustrating the nuances and robusticity of social ecology in indigenous subsistence economies.